Reward : (MacMillan, 1994)
Designed to take students from their first introduction to English up to a proficient use of the language, this multi-level course offers choice and flexibility. The 70-hour core syllabus in the student's book allows swift progression with its essential grammar points, systematic vocabulary and skills development, and regular progress checks. There are two resource packs at each level - a general-English pack and a business-English pack. Each contains photocopiable communicative activities which can be used to supplement the core syllabus in the student's book, revise specific language and structures, and provide variety in class. Other materials at each level are a practice book for self-study, a spiral-bound teacher's book which is interleaved with the student's book, two class cassettes and a practice-book cassette. This is the pre-intermediate-level student's book.